2021
DOI: 10.1002/joc.7264
|View full text |Cite
|
Sign up to set email alerts
|

Future changes in precipitation extremes across China based on CMIP6 models

Abstract: A comparison assessment of model capabilities in simulating precipitation extremes across China was first implemented by using 30 models from the Coupled Model Intercomparison Project Phase 5 (CMIP5) and using 36 CMIP6 models. The results indicate that the multi‐model median ensembles (MME) of both the CMIP5 and CMIP6 models can reasonably reproduce the climate means for the period from 1986 to 2005, and the biases are lower in most CMIP6 models compared to the CMIP5 models, especially over southern China. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 38 publications
8
27
0
Order By: Relevance
“…It would be up to 2 days and 3–4 days over southern China in the mid-term and long-term periods. The above results are consistent with the conclusions of Xu et al [ 40 ] and Zhu et al [ 41 ].…”
Section: Future Projection Based On Downscaled Cmip6 Multi-model Ense...supporting
confidence: 94%
“…It would be up to 2 days and 3–4 days over southern China in the mid-term and long-term periods. The above results are consistent with the conclusions of Xu et al [ 40 ] and Zhu et al [ 41 ].…”
Section: Future Projection Based On Downscaled Cmip6 Multi-model Ense...supporting
confidence: 94%
“…Although the examination of the sources of the uncertainty in projections was out of scope of this study, numerous studies have indicated that internal variability in the model accounts for most sources of uncertainty as compared to scenario or inter-model uncertainty [86]. For instance, a recent study that examined future changes in precipitation extremes across China based on CMIP6 models noted that uncertainty in future projections were mainly sourced from the internal variability, which accounted for more than 50% of the total variance in the indices, except for the CDD [73].…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, uncertainty in the model spread is shown based on the 25th to 75th interquartile range for SSP2-4.5 and SSP5-8.5 scenarios for the precipitation extremes. A similar approach has been used in a recent study that explored the future changes in precipitation over China based on CMIP6 models [73]. The precipitation indices of PRCPTOT, R20 mm, and SDII are projected to significantly increase under both scenarios (Figure 4a,c,d).…”
Section: Future Changes In Long-rain Seasonmentioning
confidence: 94%
“…The projected increase in precipitation in the Yellow River and Haihe River Basins can also be observed in a CMIP6 GCM ensemble according to Tian et al [54]. It is worth noting that although the projected precipitation increase in the Tarim Basin is within 0.3 mm/day, the percentage change could be large considering its low annual average total precipitation, which is why several studies (e.g., [55,56]) identified it as an area vulnerable to climate change. Precipitation increase has been shown to be among the driving factors for the increased flood frequency in the Tarim River Basin since the 1980s [57]; the increase in future precipitation as projected by this and the previous studies may indicate increased flood risks in this area, which suggests the need for relevant flood prevention measures.…”
Section: Discussionmentioning
confidence: 78%